Выплавка титановых сплавов (обзор) - Червоный, Иван Федорович; Голобородько, Елизавета Арсеньевна; Мамотенко, Владлена Игоревна (НТУ "ХПИ", 2015)
Выполнен анализ технологий и технологического оборудования для выплавки сплавов на основе титана с использованием металлического титана и титана из вторичного сырья. Исходя из требуемых механических и физико-химических характеристик сплавов на основе титана определены преимущественно целесообразные направления использования электронно-лучевой и индукционной плавки разнообразного исходного сырья с обеспечением заданных свойств конечного продукта. При производстве сплавов на основе титана предусматривается обработка металлического титана в виде титановой губки или переработка титана из вторичного сырья–лома и отходов промышленности.

The analysis of technologies and technological equipment is executed for smelting of alloys on the basis of titan with the use of metallic titan and titan from secondary raw material. On the basis of the required mechanical and physical and chemical descriptions of alloys on the basis of titan mainly expedient directions of the use of the cathode-ray and induction melting of various feedstock are certain with providing of the set properties of the finished good. At the production of alloys on the basis of titan treatment of metallic titan as a titanic sponge or processing of titan is foreseen from secondary raw material-crow-bar and wastes of industry. First of all the task of sorting of initial raw material, both primary and secondary, and preparation of charge decides for melting. After the special preparation a charge yields to the affinage from gaseous admixture-oxygen, nitrogen and hydrogen. Thus, in the process of affinage the operation of alloying is foreseen for providing of necessary descriptions of alloy. From numerous technological receptions and methods of smelting of alloys on the basis of titan two is distinguished anchorwomen processes are cathode-ray and induction methods of processing of initial raw material as titanic bars, spongy titan or titan from secondary raw material. These methods provide the high measure of cleanness of process, accessible structural implementation asms for melting of metal and high enough and guided yield.
Smelting of titanic alloys (review)
Keywords: титан; электронно-лучевая плавка; индукционная плавка; титановая губка; вторичное сырье; titan; cathode-ray melting; induction melting; crow-bar; wastes